Effects of logging residue on the growth and properties of the humus layer in Scots pine and Norway spruce stands - Mäkinen, Harri; Smolander, Aino (Elsevier, 2025)
The utilisation of forest-based primary biomass as a source of renewable energy is becoming increasingly prevalent as a means of reducing the reliance on fossil fuels. However, there has been a growing concern about the potential impact of increased organic matter and nutrient removal on long-term forest productivity. The objective of this study was to investigate the impact of logging residue removal on stand productivity and soil C and N levels in Finland. The material was collected from young Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies (L.) Karst.) stands 20–21 years following the final felling, as well as from a pine experiment that was established in conjunction with an intermediate thinning 20 years ago. In the young stands after final felling, the treatments were whole-tree harvesting, stem-only harvesting, and stem-only harvesting with a double amount of logging residues left on the plots. In the middle-aged stand after thinning, the residue levels were 0, 10, 20, and 30 Mg ha−1. In the young spruce stands, the removal of logging residue following the final felling resulted in a negative growth response, but the doubling of logging residue did not result in a further growth increase. In contrast, no treatment effects were observed in the growth of the Scots pine stands, both in the young stands after final felling and in the middle-aged stand after thinning. In the young stands after final felling, the logging residues had no significant impact on the amounts of humus layer C or N. In contrast, the logging residues increased the levels of both C and N in the humus layer of the middle-aged pine stand after thinning. It can be concluded that the removal of nutrients following the harvest of logging residue in final felling and thinning does not indicate significant issues with regard to the availability of nutrients, based on the data on tree growth.
Keywords: forest soil; logging residues; nutrients (plants); Picea abies; Pinus sylvestris; tree growth